Correlates of Women’s Labor Force Supply in Pakistan - Awan, Abdul Ghafoor; Faridi, Zahir; Bibi, Shazia (Global Disclosure of Economics and Business, 2016)
This study has analyzed correlation among those variables that affect women working hours in labor market in Pakistan. We used primary data that was collected from the rural and urban areas of District Multan. A sample of 300 women having eight years education was taken randomly and formal questionnaire was constructed for this purpose. Ordinary Least Square method was applied for estimation of parameters. The results of our empirical study show that various variables have expected signs in analysis. We found that joint family setup, family expenditures, number of dependent, working days and wage rate impact positively and significantly to the working hours of women. In contrast, number of children, nuclear family size, etcare inversely related to the women working hours. Therefore, we suggest that there should be provision of better education for women to improve their working hours and participation rate in labor market.